Our experience of combined treatment of chronic central serous chorioretinopathy using laser exposure of different wavelengths - A. Y. Tikhonova; N. A. Pozdeyeva; N. P. Pashtaev (Acta Biomedica Scientifica, 2022)
Central serous chorioretinopathy is a disease that occurs in young people and causes a significant decrease in visual functions. In some cases, the pathological process acquires a chronic course, the treatment of which remains an urgent problem. Unfortunately, the available methods of conservative treatment of this problem do not have proven effectiveness, and laser treatment methods do not always lead to rapid and persistent remission and do not guarantee the absence of relapses of the disease.The aim of this study. To evaluate the effectiveness of the treatment of this pathology using a combined treatment method: a combination of transpupillary thermotherapy of the optic nerve disc with micropulse laser exposure to the retinal neuroepithelial detachment zone in the treatment of patients with chronic central serous chorioretinopathy.Patients with chronic central serous chorioretinopathy were divided into two groups: patients who were treated with simultaneous application of laser exposure in micropulse mode (wavelength – 577 nm) with a single session of transpupillary thermotherapy on the optic nerve disc area (wavelength – 810 nm); and patients whose treatment consisted in laser exposure in micropulse mode (wavelength – 577 nm). In patients of the combined laser treatment group, there was an improvement in visual acuity after a month and a half from the start of therapy in 84 % of cases, whereas in patients who received only micropulse laser exposure it happened in 57 % of cases. A noticeable improvement in the linear blood flow rate in the posterior short ciliary arteries according to the ultrasound triplex examination of the eye vessels was also observed in the combined treatment group: the blood flow rate increased by 36 %, in the other group the blood flow rate did not significantly change. Also, in the combination therapy group, only 1 relapse of the disease was detected within 24 months, while in the second group, relapses were observed in 8.7 % of cases. Subjectively, patients from the combined treatment group noted a faster disappearance of complaints of visual discomfort.